PROTECTION OF FORCED MIGRANTS WITH IRREGULAR STATUS DURING THE PANDEMIC GENERATED BY COVID-19: AN ANALISYS OF THE INTER-AMERICAN COURT OF HUMAN RIGHTS ON MIGRANTS’ RIGHTS - Vieira Brigido, Eveline; Wust Zibetti, Fabíola (Novos Estudos Jurídicos, 2020)
This article analyzes the protection of forced migrants with irregular status, in times of a pandemic, based upon an analogy with cases of the Inter-American Court of Human Rights on migrants’ rights. First, this article analyzes the relationship between the migration crisis and the health crisis. Next, it studies the vulnerability and legal protection of forced migrants, according to international and regional legal documents and the decisions of the Inter-American Court of Human Rights. These documents and decisions are then interpreted, seeking to understand the protection of migrants in times of pandemic. This article concludes that forced migrants with irregular status have the same rights as nationals and migrants with regular status during the pandemic period, but that the difficulty lies in the realization of such rights.